1987
DOI: 10.1111/j.1440-1681.1987.tb00967.x
|View full text |Cite
|
Sign up to set email alerts
|

Acute Haemodynamic and Hormonal Effects of Oral Doxazosin in Normal Subjects

Abstract: Haemodynamic and hormonal effects of doxazosin, a long-acting alpha 1-adrenoceptor antagonist (2 mg) were compared with placebo in six normal men. Doxazosin at 2 mg produced lower supine systolic blood pressure and plasma cortisol concentration than control at 4 h only, but these changes were not sustained. Both supine and standing pulse rate were increased by active drug after 6 h. In this acute study doxazosin did not affect plasma renin or aldosterone concentrations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…The effect of doxazosin on the ARR is very small, as also observed after acute and chronic usage. 20,21 In contrast, the effect of fosinopril on ARR is more evident but does not result in any false diagnosis of essential hypertension in patients with PA. This is in agreement with the proposal that ACE-Is can be used to confirm the diagnosis of PA. 30,31 Previous studies have shown that ACE-Is, such as enalapril, are effective in reducing blood pressure and aldosterone secretion in patients with PA. 32 This could be owing to the inhibition of angiotensin II generation, to which IHA patients display enhanced sensitivity.…”
Section: Discussionmentioning
confidence: 97%
“…The effect of doxazosin on the ARR is very small, as also observed after acute and chronic usage. 20,21 In contrast, the effect of fosinopril on ARR is more evident but does not result in any false diagnosis of essential hypertension in patients with PA. This is in agreement with the proposal that ACE-Is can be used to confirm the diagnosis of PA. 30,31 Previous studies have shown that ACE-Is, such as enalapril, are effective in reducing blood pressure and aldosterone secretion in patients with PA. 32 This could be owing to the inhibition of angiotensin II generation, to which IHA patients display enhanced sensitivity.…”
Section: Discussionmentioning
confidence: 97%
“…Similarly, numerous studies in humans have shown that the α 1 antagonists terazosin (Beretta-Piccoli et al, 1986), prazosin (Falch et al, 1979), and doxazosin (Oliveros-Palacios et al, 1991) reduce BP without any effect on peripheral aldosterone levels. Finally, research has shown that doxazosin administration does not result in sustained changes in either cortisol or aldosterone levels (Whitworth et al, 1987). In addition, the lack of changes in serum cortisol baseline levels may also reflect, at least in part, the absence of clinically-significant alcohol withdrawal during the study (Costa et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…71 Alpha-blockers such as doxazosin are associated with minimal decreases in aldosterone and ARR. [71][72][73] Thiazide diuretics can also cause a reduction in the ARR. 74,75…”
Section: Limitations/strengths Of This Studymentioning
confidence: 99%